Biological aspects of Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) fed with Planococcus citri (Risso, 1813) (Hemiptera: Pseudococcidae) and Toxoptera citricida (Kirkaldy, 1907) (Hemiptera: Aphididae) - Bonani, Jean Patrick; Souza, Brígida; Santa-Cecília, Lenira Viana Costa; Correa, Lilian Roberta Batista [UNESP] (FapUNIFESP (SciELO), 2009)
The citrus-growing ecosystem houses a great deal of species of natural enemies, among them Chrysoperla externa (Hagen, 1861), which presents a great potential for use in the biological control of pests. The aim of this work was to evaluate the effects of the preys Planococcus citri (Risso, 1813) and Toxoptera citricida (Kirkaldy, 1907) on the development of larva and pupa of C. externa. The trial was carried out in an acclimatized room at 25±1°C, 70±10% RH and 12-hour photophase, the treatments consisting of the continuous and alternate supply of those two preys in each instar of the predator, in addition to eggs of Anagasta kuehniella (Zeller, 1879) utilized for comparison purposes. Both the white mealybug and the aphids were given in sufficient amounts to the C. externa larvae to be able to feed ad libitum. The lifetime and the survival rate of the phases of larva, pupa and the larval-adult period of C. externa were evaluated. It was found that T. citricida given either singly along the larval development or in two consecutive instars of the predator was not an adequate prey, 100% of mortality over the larval-adult period being found. When the larvae fed on P. citri, given in two instars of the predator, the survival rate in the larval-adult period was similar to the diet constituted of only A. kuehniella eggs, except when fed with T. citricida in the first instar.
Aspectos biológicos de Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) alimentada com Planococcus citri (Risso, 1813) (Hemiptera: Pseudococcidae) e Toxoptera citricida (Kirkaldy, 1907) (Hemiptera: Aphididae)
Keywords: Aphid; Biology; Citrus; Green lacewing; White mealybug